Comparing the effectiveness of compassion - focused therapy and mindfulness training on post - traumatic developmental disorder and cancer burnout in cancer patients - Atousa Sadeghpour; javad khalatbari; Ali Akbar Seif; Ali Shahriariahmadi (مجله علوم روانشناختی, 2020)
Background: Cancer-related burnout is one of the factors affecting the mental health of people with cancer. But the key question is whether compassion-focused therapy and mindfulness training can affect traumatic development and burnout in people with cancer? Aims: To compare the effectiveness of therapy focused on compassion and mind training on traumatic development and cancer-related burnout in cancer patients. Method: The experimental design was pre-test and post-test. The statistical population included all cancer patients of Prophet Akram Hospital who were referred for chemotherapy in 1396. Sixty subjects were selected by purposive sampling method and were randomly divided into three groups of 20 (two experimental and one control group). Instruments include the Teddych & Kahlone Trauma Disaster Questionnaire (1996) and the Okimama et al. Cancer Burnout Scale (2000), Mindfulness-Based Intervention (Bayer, 2014), and Gilbert Compassion Therapy Intervention (2005). Data were analyzed by multivariate analysis of covariance, extrapolated follow-up test and L-matrix. Results: Mindfulness-awareness and compassion-focused therapy had a significant effect on increasing traumatic development and decreasing burnout in patients (P<0/01). Also, mindfulness training on post-traumatic development was more effective than compassionate focused therapy, but there was no difference between the effectiveness of the two methods on cancer-related burnout (P<0/01). Conclusions: Mindfulness training and compassion-focused therapy interventions can be used to increase traumatic development and reduce burnout in cancer patients.